Coping strategies of individuals living with excretory stomas and associated factors: a cross-sectional study (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To analyze the coping strategies of individuals living with excretory stomas in a specialized public healthcare service within the Brazilian Unified Health System (Sistema Único de Saúde – SUS). Method: This cross-sectional study included 201 individuals with digestive and/or urinary stomas, regardless of etiology. A sociodemographic and clinical questionnaire was used, along with the Problem Coping Modes Scale, which assesses four types of focused coping strategies: problem-focused (factor 1), emotion-focused (factor 2), pursuit of religious practices/imaginative thinking (factor 3), and search for social support (factor 4). Results: The following means were observed: factor 1 (4.19), factor 2 (1.81), factor 3 (3.84), and factor 4 (2.61). Factor 1 showed associations with age (p=0.04), employment status (p=0.05), and surgery preparation (p=0.05). An association was found between factor 2 and age (r=-0.14; p=0.04), income (p=0.003), practice of physical activity (p=0.04), and number of ostomy pouches used (p=0.01). Factor 3 was found to be associated with gender (p=0.02), age (p=0.02), income (p=0.04), stoma duration (p=0.04), cause of stoma creation (p=0.01), stoma type (p=0.04), and number of pouches used per month (p=0.01). Factor 4 showed associations with age (r=-0.194; p=0.006) and stoma duration (p=0.03).Conclusion: A lack of prior preparation was identified among individuals living with a stoma. Understanding coping strategies and patient profiles is essential for developing effective interventions focused on support and psychoeducation.